2022
DOI: 10.1186/s13063-022-06516-1
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of trial protocols approved by research ethics committees: The Adherance to SPIrit REcommendations in the UK (ASPIRE-UK) study

Abstract: Background To assess the quality of reporting of RCT protocols approved by UK research ethics committees before and after the publication of the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guideline. Methods We had access to RCT study protocols that received ethical approval in the UK in 2012 (n=103) and 2016 (n=108). From those, we assessed the adherence to the 33 SPIRIT items (i.e. a total of 64 components of the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, this is likely a critical step in increasing awareness, uptake, and adherence to the newly developed SPIRIT/CONSORT-C to improve reporting comprehensiveness in future trial protocols and reports. However, endorsement from journals is not sufficient, particularly for trial protocols, as adherence to SPIRIT guidelines is still suboptimal [ 77 ]. While trial protocols are often reviewed at early stages by funders, Institutional Review Boards, and regulatory bodies, these early review efforts need to be more transparent, connected, and require structured guidelines for peer review [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this is likely a critical step in increasing awareness, uptake, and adherence to the newly developed SPIRIT/CONSORT-C to improve reporting comprehensiveness in future trial protocols and reports. However, endorsement from journals is not sufficient, particularly for trial protocols, as adherence to SPIRIT guidelines is still suboptimal [ 77 ]. While trial protocols are often reviewed at early stages by funders, Institutional Review Boards, and regulatory bodies, these early review efforts need to be more transparent, connected, and require structured guidelines for peer review [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the 10 most important and poorly reported items for CONSORT-PR was completely based on previous literature. 18 For SPIRIT-PR, we considered all available assessments of reporting 19 , 20 , 21 and chose 10 items through a consensus process within the study team. More details on this process as well as the development of a brief description for each item is presented in eAppendix 3 in Supplement 3 .…”
Section: Methodsmentioning
confidence: 99%
“…However, uptake of J o u r n a l P r e -p r o o f SPIRIT by trialists has been limited. Moreover, a recent randomized controlled trial (RCT) has shown that adherence to those guidelines is not effective (6).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%